2020
DOI: 10.1038/s41562-020-00944-2
|View full text |Cite
|
Sign up to set email alerts
|

Population-scale longitudinal mapping of COVID-19 symptoms, behaviour and testing

Abstract: Despite the widespread implementation of public health measures, COVID-19 continues to spread in the United States. To facilitate an agile response to the pandemic, we developed How We Feel, a web and mobile application that collects longitudinal self-reported survey responses on health, behavior, and demographics. Here we report results from over 500,000 users in the United States from April 2, 2020 to May 12, 2020. We show that self-reported surveys can be used to build predictive models to identify likely C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
147
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(162 citation statements)
references
References 59 publications
13
147
1
1
Order By: Relevance
“…Alternatively, if the appropriate comparison group is not available, one can consider creating a model for who was tested and use the inverse probability weighting approach to adjust for the selection bias due to prioritized testing guidelines. 53 In general, our findings are consistent with existing studies. Male sex was associated with a higher risk of hospitalization and death, especially among individuals 50 years and older.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, if the appropriate comparison group is not available, one can consider creating a model for who was tested and use the inverse probability weighting approach to adjust for the selection bias due to prioritized testing guidelines. 53 In general, our findings are consistent with existing studies. Male sex was associated with a higher risk of hospitalization and death, especially among individuals 50 years and older.…”
Section: Discussionsupporting
confidence: 93%
“…In children, the result was not statistically significant, possibly due to a small sample size. Although anosmia and ageusia were initially less described as COVID-19 symptoms 3,6 , and were not part of the Israeli testing policy throughout the study period, they further emerged as the most predictive symptoms for COVID-19 in this study and others 10,12,22 , and were also found to be the most prolong symptoms in infected individuals 23 . Health organizations worldwide have gradually added it to the list of COVID-19 related symptoms including the USA CDC 24 , the UK 25 and Israel 26 .…”
Section: Discussionmentioning
confidence: 53%
“…In this study, we have demonstrated the use of population-wide data reported through the COVID Symptom Study app, drawing on more than 120 million daily reports and about 170 000 invited swab tests from more than 2·8 million users to estimate prevalence, incidence, and R(t). Other digital surveys have been used to provide valuable real-time information about the pandemic, including How We Feel, 20 Corona Israel, 5 the Facebook Survey , and CovidNearYou . However, to our knowledge we are the first to provide national-level disease surveillance, and we have found good agreement with traditional, representative community surveys.…”
Section: Discussionmentioning
confidence: 99%